LOCALITY PERCEPTION OF WOMEN FOR SQUATTER AND APARTMENT: THE CASE OF ANKARA AKŞEMSETTIN NEIGHBORHOOD - Elif ERTEM (Fırat University, 2019)
Akşemsettin neighborhood that is exposed to urban transformation and gecekondu-apartment experiences and perception of women living in this transformation area are examined in the study. Squatters (gecekondu) are transformed to apartment buildings through urban transformation project. Even though project in neighborhood has been finished, there are still limited areas where gecekondu and apartments can be found together. This study is conducted survey with different age house women-no regular income work- lived in gecekondu before the project and now living in apartments and conducted survey with women still living in gecekondu. The study conducted in May-July 2016 in Akşemsettin neighborhood, in the line of Ankara, Ege Neighborhood and it is conducted survey with 360 women. In the context of experience of women life in gecekondu and apartment, starting from how this transformation affects the practice and experience of womanhood, the study aims to investigate urban transformation, experience, and perception of women. How urban transformation prospect differentiation on spatiality of the house through the women’s practice and experience of their family, friendships, fellowships and their relationships with children and education of children. Gecekondu and apartments are not only physically different area; they give references to social relationships and social production area. From that point, the study taking from gecekondu and apartment neighborhood on the comparison of gecekondu and apartment through the analyses of survey via SPSS program investigate experience and perception of women and gecekondu and apartment neighborhood in district and so, the study tries to contribute the literature of urban transformation from the discourse of women.